Harvard, the Chicago tradition and the quantity theory: A reply to James Ahiakpor - David Laidler; Roger Sandilands (The University of Western Ontario, Department of Economics, 2010)
James Ahiakpor's critique of our 2002 work on the relationship between a certain 1932 Harvard Memorandum on anti-depression policies and the 1932 Harris Foundation Manifesto dealing with the same issues misses the significance of these documents, and of the relationships between them, both for the literature of the time, and for later debates about the origins of 1930s Chicago ideas about monetary economics. He is correct to locate these documents in a more general quantity theoretic tradition, but his discussion here is marred by a serious misunderstanding of the so-called forced saving doctrine and its place in that tradition. Finally, Ahiakpor fails to appreciate that the absence of positive policy proposals from the 1934 Harvard studies of The Economics of the Recovery Program, a point which he himself notes, is a major contributing factor to that book's mediocrity.
Keywords: B12; B22; E52; 330; Chicago tradition; quantity theory; forced saving; depression; Wirtschaftswissenschaft; Wirtschaftskrise; Wirtschaftspolitik; Monetarismus; Dogmengeschichte; USA